Cold plasma pretreatment improves the quality and nutritional value of ultrasound-assisted convective drying: The case of goldenberry. Issue 8 (15th June 2022) - Miraei Ashtiani, Seyed-Hassan; Rafiee, Mahta; Mohebi Morad, Mina; Martynenko, Alex
Abstract: Nutrient damage and high energy consumption are the challenges of convective drying to achieve food security and economic stability. Wild berries have high nutritional value, but they are difficult to dry because of the waxed skin tissue. Such a cellular structure is highly resistant to mass transfer, which increases drying time and nutrient degradation. Although chemical pretreatments can facilitate a mass transfer, they reduce the amounts of soluble nutrients. As an alternative, we propose an innovative strategy with cold plasma pretreatment followed by ultrasound-assisted convective drying. Cold plasma pretreatment enabled reducing drying temperature from 60–90 °C to 50 °C, which improved the nutritional quality of the dried goldenberries. The application of ultrasound energy significantly reduced drying time. Compared to the untreated convective dried samples, the vitamin C retention, antioxidant activity, and total phenolic content increased by up to 175.07%, 84.32%, and 52.31%, respectively. This drying approach can significantly contribute to food security by improving product quality, nutritional value, shelf stability, and reducing greenhouse gas emissions.